Efficacy of Eye Movement Desensitization and Reprocessing in Children and Adolescent with Post-traumatic Stress Disorder: A Meta-Analysis of Randomized Controlled Trials - Moreno-Alcázar, Ana; Treen, Devi; Valiente-Gómez, Alicia; Sio-Eroles, Albert; Pérez, Víctor; Amann, Benedikt L.; Radua, Joaquim (Frontiers in Psychology, 2017)
Background: Posttraumatic Stress Disorder (PTSD) can occur in both adults and children/adolescents. Untreated PTSD can lead to negative long-term mental health conditions such as depression, anxiety, low self-concept, disruptive behaviors and/or substance use disorders. To prevent these adverse effects, treatment of PTSD is essential, especially in young population due to their greater vulnerability. The principal aim of this meta-analysis was to examine the efficacy of Eye Movement Desensitization and Reprocessing (EMDR) therapy for PTSD symptoms in children and adolescents. Secondary objectives were to assess whether EMDR therapy was effective to improve depressive or anxious comorbid symptoms. Methods: We conducted a thorough systematic search of studies published until January 2017, using PubMed, Medline, Scopus and ScienceDirect as databases. All randomized controlled trials with an EMDR group condition compared to a control group, such as treatment as usual or another psychological treatment, were included. Meta-analysis was conducted with MetaNSUE to avoid biases related to missing information. Results: Eight studies (n=295) met our inclusion criteria. EMDR therapy was superior to waitlist / placebo conditions and showed comparable efficacy to cognitive-behavioral therapy (CBT) in reducing post-traumatic and anxiety symptoms. A similar but non-statistically-significant trend was observed for depressive symptoms. Exploratory subgroup analyses showed that effects might be smaller in studies that included more males and in more recent studies. Conclusions: Despite the small number of publications, the obtained results suggest that EMDR therapy could be a promising psychotherapeutic approach for the treatment of PTSD and comorbid symptoms in young individuals. However, further research with larger samples is needed to confirm these preliminary results as well as to analyze differences in the efficacy of EMDR therapy versus CBT.